Analisis Minimalisasi Biaya Penggunaan Antiplatelet Pada Pasien Stroke Infark Rawat Inap - Wicaksono, Ayssa; Rachmawati, Ema; Norcahyanti, Ika; Aryani, Dhita Evi; Machlaurin, Aﬁfah (Faculty of Pharmacy, University of Jember, 2024)
Antiplatelets are crucial medications in the treatment of ischemic stroke patients. The management of stroke cases in Indonesia incurs substantial costs, reaching Rp. 3.2 billion annually. This study conducted a simple pharmacoeconomic research using Cost Minimization Analysis (CMA) method, utilizing medical records and patient ﬁnancing data of ischemic stroke inpatients at RSUD Gambiran, Kediri City from January to December 2022. The study adopts a hospital perspective with the same outcome of patient recovery. Out of 659 stroke patients, 100 eligible participants, predominantly male aged 46-65 years with Diabetes Mellitus as the most common comorbidity, were included. Based on antiplatelet therapy proﬁles, the majority received a combination of clopidogrel and aspirin (65%), while 35% received clopidogrel monotherapy. The largest cost component was service cost amounting to Rp 2,898,606 (59.37%). According to CMA analysis, combination therapy showed cost-saving beneﬁts compared to monotherapy in drug and medical equipment, laboratory, service, and total overall costs. Thus, for ischemic stroke patients with the same outcome of recovery, combination therapy of clopidogrel and aspirin isrecommended over clopidogrel monotherapy.